The HyperVerse: concepts for a federated and Torrent-based '3D Web'. (29th December 2008) - Botev, Jean; Hohfeld, Alexander; Schloss, Hermann; Scholtes, Ingo; Sturm, Peter; Esch, Markus
The vision of a '3D Web' as a combination of massive online virtual environments and today's WWW currently attracts a lot of attention. While it provides a multitude of opportunities, the realisation of this vision on a global scale poses severe technical challenges. This paper points out some of the major challenges and highlights key concepts of an infrastructure that is being developed in order to meet them. Among these concepts, special emphasis is put on the usage of a two-tier Peer-to-Peer approach, the implementation of Torrent-based data distribution, and the development of a graded consistency notion. The paper presents the current state of a prototype implementation that is being developed in order to validate these concepts and evaluate alternative approaches.